2012
DOI: 10.1177/1403494812467503
|View full text |Cite
|
Sign up to set email alerts
|

Does quality of life of prostate cancer patients differ by stage and treatment?

Abstract: Our study highlighted statistically significant differences in QoL between cancer stages and treatment. Understanding how the QoL changes in relation with the selected treatment option can be important to the urologist and individual patient to have realistic expectations as well as to optimise treatment decisions for the prostate cancer patient when exist several alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…In social functioning, the RP group does not substantially improve over time and a substantial gap between RP and AS patients' remains up to 3.5 years after diagnosis. Our present results mainly concur with the results of Vanagas et al [13] and their cross-sectional study that also used the EORTC QLQ-C30. There, patients under AS reached statistically and clinically significantly better levels in role, social and emotional functioning than patients under RP or HT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In social functioning, the RP group does not substantially improve over time and a substantial gap between RP and AS patients' remains up to 3.5 years after diagnosis. Our present results mainly concur with the results of Vanagas et al [13] and their cross-sectional study that also used the EORTC QLQ-C30. There, patients under AS reached statistically and clinically significantly better levels in role, social and emotional functioning than patients under RP or HT.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies showed similar oncological outcomes for AS and RP in low-risk prostate cancer [9][10][11]. A negative impact on HRQOL has so far not been demonstrated [6,12,13]. The assumption that knowledge of having an untreated disease leads to higher levels of anxiety in AS patients has been disproven by several studies [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…No major differences were observed between the HRQoL scores of AS patients and their comparison groups [19,21,23,25,26]. There were also no major changes in HRQoL after 9 or 12 mo on AS in two PRIAS cohorts [24,26].…”
Section: Overall Health-related Quality Of Lifementioning
confidence: 49%
“…Finnish men in the PRIAS also reported higher scores than a population sample at baseline and follow-up assessments, which the authors suggested may result from men with favourable psychological characteristics choosing AS. Vanagas et al [25] highlighted that men on AS reported significantly better HRQoL than men who underwent radical treatment in both functional and symptom scales, although these results by treatment group were not subdivided by tumour stage. Bellardita et al [18] found that high levels of HRQoL were predicted by a patient having consulted several physicians about the choice of AS, by the presence of a partner, and a diagnostic biopsy with >18 core specimens.…”
Section: Overall Health-related Quality Of Lifementioning
confidence: 96%
“…HRQoL in PCa can also be influenced by factors such as tumor level, time elapsed since diagnosis, individual factors such as educational level and social background, age at diagnosis, and treatment type [8, 12, 13]. For example, patients with stage I tumor exhibited higher HRQoL scores compared to those with tumor stage IV [12]. Men with advanced PCa face severe and several health- and treatment-related problems compared with men with localized PCa [14].…”
Section: Introductionmentioning
confidence: 99%